Of laughter and tears a memoir - Joaquin, Sarah K. (Carayan Press, 2007)
This volume about the life of Sarah K. Joaquin traces a memorable childhood from Sta. Cruz, Laguna, to school at Centro Escolar and the University of the Philippines. She became a teacher, freelance writer, translator, stage actress and drama director. She was fluent in Spanish, English and Filipino. Establishing a lasting legacy in the Philippine theater world, Joaquin emigrated to the USA in the later years of her life, where she wrote this autobiography before passing away at the age of 92.